Plagues : the microscopic battlefield - Koch, Falynn, 1985- (Science comics (First Second (Firm)), 2017)
Presents an introduction to plagues that have devastated communities throughout history. Explores the critters that spread the worst disease and the advances in medical science that have allowed us to eradicate and survive such ailments. Includes a glossary, timeline, diagrams, and resources for further information.